"Walking Blindly Into It": Library Administrators and Renovations. Issue 3 (3rd April 2021) - Elrod, Rachael
Abstract: This study seeks to understand the experiences of library administrators who have led a major library renovation project. Most often this person is an Associate Dean working on the Dean's behalf. Six participants from large, public, research universities in the United States were interviewed for this study. The findings show that library administrators are largely unprepared to lead renovations in terms of formal education and training. Suggestions are offered to help library administrators become better prepared in areas related to renovations and provide implications in terms of funding, staffing practices, professional development, and organizational understanding.